Increased blood-derived mitochondrial DNA copy number in African ancestry individuals with Parkinson's disease. (August 2022) - Müller-Nedebock, Amica Corda; Meldau, Surita; Lombard, Carl; Abrahams, Shameemah; van der Westhuizen, Francois Hendrikus; Bardien, Soraya
Abstract: Introduction: Altered levels of mitochondrial DNA copy number (mtDNA-CN) have been proposed as a proxy for mitochondrial dysfunction. Following reports of mtDNA depletion in the blood and substantia nigra of Parkinson's disease (PD) cases, mtDNA-CN was also suggested as a possible biomarker for PD. Therefore, this study aimed to investigate whether blood mtDNA-CN levels of African ancestry PD cases would be altered compared to controls, as previously reported in individuals of Asian and European ancestry. Methods: Droplet digital polymerase chain reaction (ddPCR) was performed to quantify blood-derived mtDNA-CN levels as a ratio of a mitochondrial gene ( MT-TL1 ) to a nuclear gene ( B2M ) in 72 PD cases and 79 controls of African ancestry (i.e. individuals with African mtDNA haplogroups) from South Africa. mtDNA-CN per cell was calculated by the formula 2 ×  MT-TL1 / B2M . Results: Accepting study limitations, we report significantly higher mtDNA-CN in whole blood of our PD cases compared to controls (median difference = 81 copies/cell), independent of age (95% CI [64, 98]; P < 0.001]). These findings contradict previous reports of mtDNA depletion in PD cases. Conclusions: We caution that the observed differences in mtDNA-CN between the present and past studies may be a result of unaccounted-for factors and variability in study designs. Consequently, larger well-designed investigations may help determine whether mtDNA-CN is consistently altered in the blood of PD cases across different ancestries and whether it can serve as a viable biomarker for PD. Graphical abstract: Image 1 Highlights: mtDNA-CN was quantified in African ancestry PD cases and controls using ddPCR. PD cases had significantly higher levels of mtDNA-CN than controls. Age-adjusted analysis revealed 81 mtDNA copies/cell more in cases than controls. Variability of blood mtDNA-CN may limit its use as a PD biomarker.